Weltbühne Zürich: Kurt Hirschfeld und das deutschsprachige Theater im Schweizer Exil - Wildmann, Daniel; Gross, Raphael (Mohr Siebeck, 2022)
Theatre director Kurt Hirschfeld shaped German-language theatre like no other during its Swiss exile and beyond. This volume explores the fragile experience of exile of one of German-Jewish historys key figures, and examines his intellectual network which comprised such authors as Bertolt Brecht and Max Frisch.
PublicationDate: 20220630
Keywords: Nationalsozialismus -- Antisemitismus -- Biographie -- Widerstand -- Theatergeschichte -- Iron Age -- Neuzeit -- Sozial-/Kulturwissenschaften -- 19.-21. Jahrhundert -- Jüdische Geschichte